PENGEMBANGAN BUKU SUPLEMEN IPA UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI GETARAN DAN GELOMBANG SISWA KELAS VIII MTsN 6 NGANJUK - Muna, Chusna Lailatul; Yusal, Yulianti; Wulandari, Ratna Wahyu (Universitas Tanjungpura, 2025)
This study aims to describe the results of the development of science supplement books on vibration and wave materials to improve student learning outcomes. This research was conducted at MTsN 6 Nganjuk grade VIII. The method used in this study is R&D (Research and Development) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The research subjects in this study are students in grades VIII-2 even semester of the 2024/2025 academic year totaling 30 students. The results of the research from the development of this Science Supplement book are (1) The development of the Science Supplement Book is made with the addition of a QR code feature that leads to vibration and wave simulation, and is equipped with practice questions for each chapter, enrichment exercises, remidials, quizzes, LKPD and a collection of 100 wave vibration questions so that students can learn independently to improve student learning outcomes (2) Validation by teaching material experts shows the feasibility of the Science Supplement Book by percentages of 90% and 95.7%, while subject matter experts gave assessments of 61.4% and 91.4%. Analysis of pretest and posttest data showed an increase in student learning outcomes, with an average pretest score of 53.3 increasing to 81.3. (3) then the researcher performed the Wilcoxon parametric one test and obtained the result of the Asymp. Sig. (2-tailed) value was